Knowledge and Attitude of Dentists and Patients Toward Use and Health Safety of Dental Amalgam in Saudi Arabia - Al-Nahedh, Hend N.; El-hejazi, Ahmed A; Habib, Syed Rashid (European Journal of Dentistry, 2020)
Objective The aim of this study was to assess: (1) the perceptions of dentists in Saudi Arabia concerning the amalgam controversy, (2) their attitude toward the ethical responsibility of patient information, and (3) patients’ knowledge and attitude toward the use of dental amalgam.Materials and Methods A total of 1,139 dentists were sampled on convenience by electronic survey. The questionnaire contained questions about the safety of dental amalgam, use of amalgam, case selection, alternate materials, and informing their patients about risks of amalgam. Also, 425 patients were sampled on convenience and information collected on their knowledge about amalgam and its acceptance in their oral cavities.Results A total of 201 dentists and 425 patients participated in the study. A total of 60% of dentists and specialists declared it safe. A total of 32.4% (31) of general dental practitioners and 41% (43) specialists considered it a moral obligation to inform patients about the potential health risks associated with amalgam. Mercury toxicity was identified as the most common health hazard. About 57.3% dentists and 36.2% specialists opted for superior longevity as the principle advantage. Majority of patients (52.2%) in Saudi Arabia had no knowledge about dental amalgam. While 23.1% (98) had concern about poor color, 8.7% (30) knew it contained silver while only 7.8% (27) patients were aware of its mercury content.Conclusion Majority of dentists in Saudi Arabia found it safe to use amalgam while the patients had little knowledge about the possible issues with amalgam. It is recommended to improve public awareness about impact of mercury containing products on the environment.
Keywords: amalgam; dental amalgam; dentists; health safety; dental restorations; filling